Analisis kesalahan siswa dalam menyelesaikan soal cerita materi pengukuran panjang berdasarkan teori Nolting pada siswa kelas IV sekolah dasar - Nabilla Rianita; Siti Istiyati; Septi Yulisetiani (Universitas Sebelas Maret, 2024)
The research focused to (1) describe the types of student errors when solving story problems on length measurement material based on Nolting's theory, (2) describe the factors that cause errors, and (3) describe alternative solutions. The method used in this research is descriptive qualitative. The subject in this study was class IV student and class IV teacher at Ta’mirul Islam Surakarta. The data validity test technique used source triangulation technic. Data collection techniques used the results of document studies and interviews. The data analysis technique used Miles and Huberman analysis, which consists of (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawing. The results showed that most common error found was an error during the test with a percentage of 52.7%, Learning errors are the least mistakes made by students with a percentage of 0.7%.